A Rare Presentation of a Dermoid Cyst with Draining Sinus in a Child: Case Report and Literature Review. Issue 4 (14th June 2016) - Yan, Chen; Low, David W.
Abstract: Orbitofacial dermoid cysts in children are treated using surgical excision. Dermoid cysts of the frontotemporal region usually present as superficial, slow‐growing masses without deep extension. We report a rare case wherein a frontotemporal dermoid in a 21‐month‐old girl presented with a draining sinus tract to the skin and extended intracranially through the sphenoid bone. It was removed surgically and a dermoid cyst was removed from the frontotemporal region, extending superficially from the skin sinus tract through the sphenoid bone and attaching to the dura of the anterior temporal lobe. In addition to our case presentation, a literature review was performed to identify the few reported similar cases in the published literature, the combination of which suggests that frontotemporal dermoid cysts with associated draining sinus tracts may require preoperative imaging with computed tomography or magnetic resonance imaging before surgical intervention because of the high likelihood of intracranial extension.